Conditions for Consistency of Equations of Nonlinear Diffusion in Complex Systems with Thermodynamic Constraints - Sargsyan, H. P.
The paper proposes relations between the coefficients of nonlinear diffusion in complex systems within the framework of the mechanism approach of Ya. I. Frenkel for matching equations with thermodynamic constraints. Three conditions for limiting the microdescription of a complex system have been identified the fulfillment of which ensures the thermodynamically correct behavior of the equations of nonlinear multicomponent diffusion.
Keywords: Physics